Odpowiedzi

2010-04-14T17:32:21+02:00
Np.2(-1 2/3+1)-3(4*0,1+5)≤ 1 2/3+2
2010-04-14T17:46:55+02:00
X= -1¹₉
2(-1¹₉+1)-3[4*(-1¹₉)+5]≤-(-1¹₉-2)
2*(-¹₉)-3(-⁴⁰₉+⁴⁵₉)≤3¹₉
-²₉-3*⁵₉≤3¹₉
-²₉-¹⁵₉≤¹⁹₉
-¹⁷₉-¹⁹₉≤0
-³⁶₉≤0
-4≤0

x=-1²₃
2(-⁵₃+1)-3[4*(-⁵₃)+5]≤-(-⁵₃-2)
2*(-1⁵₃)-3(-²⁰₃+5)≤-(-3²₃)
-3²₃+21²₃≤3²₃
-3²₃+21²₃-3²₃≤0
14¹₃≤0

x=1²₃
2(⁵₃+1)-3(4*⁵₃+5)≤-(⁵₃-2)
2*2²₃-35≤¹₃
¹⁶₃-¹⁰⁵₃-¹₃≤0
⁹⁰₃≤0
30≤0

x=-1
2(-1+1)-3(-4+5)≤-(-1-2)
2*0-3*1≤-(-3)
-3≤3
-3-3≤0
-6≤0

x=0,01
2(0,01+1)-3(0,04+5)≤-(0,01-2)
2,02-15,12≤-(-1,99)
2,02-15,12-1,99≤0
-15,09≤0